Tinjauan Perhitungan, Pemotongan, Dan Pelaporan PPh Pasal 23 Atas Jasa Pada PT. Yudhistira Ghalia Indonesia - Nurmilawati, Nurmilawati; Riyadi, Rizal; Damatraseta, Febri (Program Vokasi dan LPPM IBI Kesatuan, 2025)
Income tax is a tax imposed on the income of a taxpayer or entity. Income tax article 23 is one of the income taxes imposed on income from capital, delivery of services, and other activities that are not included in income tax article 21. PT Yudhistira Ghalia Indonesia is a taxable company that uses the services of other companies, so the transaction is subject to income tax article 23 which will be deducted by the company. The purpose of this study is to determine how the implementation of the calculation, deduction, and reporting of Income Tax Article 23 on services at PT Yudhistira Ghalia Indonesia. The results of the review in this study indicate that PT Yudhistira Ghalia Indonesia has calculated, deducted, and reported Income Tax Article 23 on services with rates and procedures following applicable tax regulations. The company has calculated the rate for services which is 2% and has used the e-bupot unification application properly and correctly so that tax payments can be made easily.